Screening for Plasmid Mediated Antibiotic Resistance among Multi Drug Resistant Bacteria Isolated from Patients with Lower Respiratory Tract Infections Attending some Hospitals in Kano Metropolis - Mailafia, H. M.; Aminu, A. I.; Dutsinma, U. A. (UMYU Journal of Microbiology Research)
Study’s Novelty/Excerpt